2020
DOI: 10.3390/ijgi9040268
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hybrid Prediction Methods in Spatial Assessment of Inland Excess Water Hazard

Abstract: Inland excess water is temporary water inundation that occurs in flat-lands due to both precipitation and groundwater emerging on the surface as substantial sources. Inland excess water is an interrelated natural and human induced land degradation phenomenon, which causes several problems in the flat-land regions of Hungary covering nearly half of the country. Identification of areas with high risk requires spatial modelling, that is mapping of the specific natural hazard. Various external environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…Note that predictions refer to the uppermost 10 cm of the sediment layer of the lake. In addition to the spatial predictions, we also quantified the associated prediction uncertainty, which was expressed by the upper and lower limit of the 90% PI that is frequently used in environmental mapping (e.g., [27,29,48]), as presented in Figure 5 (left and right columns). Figure 6 gives a more detailed picture of the Keszthely basin where most of the N observations had to be excluded from spatial modeling and only data on P were available.…”
Section: Spatial Prediction At Point Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that predictions refer to the uppermost 10 cm of the sediment layer of the lake. In addition to the spatial predictions, we also quantified the associated prediction uncertainty, which was expressed by the upper and lower limit of the 90% PI that is frequently used in environmental mapping (e.g., [27,29,48]), as presented in Figure 5 (left and right columns). Figure 6 gives a more detailed picture of the Keszthely basin where most of the N observations had to be excluded from spatial modeling and only data on P were available.…”
Section: Spatial Prediction At Point Supportmentioning
confidence: 99%
“…Furthermore, it tries to exploit this spatial interdependence in order to give coherent and even more accurate spatial predictions for the variables of interest [23][24][25][26]. Moreover, multivariate geostatistics is able to model and quantify the uncertainty associated with a spatial prediction, which has become a common requirement in the practice of environmental modeling and mapping [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…and changes over time (causing IEW inundation, e.g. hydrometeorology, groundwater) (LABORCZI et al, 2020a;BARTA et al, 2013). BARTA et al (2016) have shown that infrastructural elements and linear facilities (road and railway network, canals, embankments, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This hydrological phenomenon practically may occur in all lowland areas with poor runoff and unfavourable water management properties of soils (LABORCZI et al, 2020a). Many approaches have been published to describe IEW which are very diverse: (1) the in situ mapping of IEW ( VAN LEEUWEN et al, 2013), (2) the determination of the extent and probability of IEW hazard (BOZÁN et al, 2018;LABORCZI et al, 2020a;LABORCZI et al, 2020b), and the modeling of its movement phenomena (KONCSOS, 2011) are the most studied topics to researchers. NAĐ et al (2018) adapted the SEERISK methodology to assess the risk of IEW appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Digital soil mapping (DSM), which has become a successful sub-discipline of soil science with an active research output [10], aims to provide spatial soil information for a wide range of studies, such as precision agriculture [11,12], hydrology [13][14][15], environmental sciences [16,17], conservation biology [18,19] or spatial planning [20,21]. For this purpose, geostatistical techniques are widely used, which have been complemented by machine learning algorithms in the past decade.…”
Section: Introductionmentioning
confidence: 99%